A formação profissional em Serviço Social: um estudo da dimensão político-pedagógica dos cursos de graduação públicos estaduais do Paraná - Faquin, Evelyn Secco (2016)
This thesis aimed at understanding the political-pedagogical dimension in the courses of Social Services of the State of Paraná University. Defining specific objectives a) contextualize how it handles vocational training in Social Work, with its legal foundations and political directions; b) map is structured as vocational training in Social Work in Public Higher Education Institutions of the State of Paraná; c) check from educational projects and curricula of undergraduate courses the elements that support the shaping of the political-pedagogical dimension of these. For construction we stop the discussion of education and University as political space par excellence that make the training process. Text looks us on vocational training and its political and pedagogical dimension by professional Ethical-Political Project. We reflect on the pedagogical projects of the courses from theoretical argument, based on the dialogue with authors of Education and Social Services, also presenting the research universe - the State Universities Paranaenses, more specifically, the social work courses in them offered. The research universe comprised eight courses of Social Service of Paraná State Universities, the Brazilian state with the largest number of public offerings of training for social workers. We have used the qualitative approach, conducting documentary research, from their pedagogical projects of the courses, so we found that the pedagogical projects have as a foundation the general context of the Brazilian university and therefore are permeated challenges; as the professional profile to be formed, they align to partially Curriculum Guidelines 1996 and showed a tendency to training geared to the labor market; the process of building these projects does not cover all the subjects involved in vocational training; and it was identified similarities between them